Assessment of Reverse Demulsifier Surfactant Performance for Emulsion Separation in Produced Water from Oil and Gas Operations - Efrian Pratiwi, Della; Chadirin, Yudi; Novriansyah, Adi; Kurniawan, Allen (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
The increasing volume of produced water from oil and gas production requires effective handling before reinjection or disposal. Produced water contains minerals, oil, and other contaminants, making separation processes at refineries insufficient. This study investigates the use of reverse demulsifiers, specifically surfactants (Alkyl Phenol Ethoxylate – APEOs and Natrium Lignosulfonate – NLS), to separate emulsions in produced water. Surfactants reduce surface tension between oil and water, facilitating contaminant removal. Using a jar test apparatus, experiments varied surfactant dosage, stirring speed, and stirring time to determine optimal conditions for achieving water quality standards. Results indicate differences between APEOs and NLS in removing contaminants. APEOs, at 5 ppm, 130 rpm, and 5 minutes, achieved a COD concentration of 80.33 mg/L, while NLS, at 5 ppm, 220 rpm, and 10 minutes, yielded 77.48 mg/L. Both are well below the quality standard of 200 mg/L, proving the effectiveness of this approach. This study highlights the potential of APEOs and NLS as reverse demulsifiers for produced water treatment. Proper application could enable safe reuse or environmentally sound disposal, providing an effective solution to managing produced water in the oil and gas industry.